Cultural influence on innovativeness: Links between "The Culture Map" and the "Global Innovation Index" - Viola Isabel Nyssen Guillén; Carsten Deckert (International Journal of Corporate Social Responsibility (JCSR), 2021)
In the ongoing debate on the relation of cultural differences and national innovativeness this research aims to find out which of the seven cultural dimensions of The Culture Map (communicating, evaluating, leading, deciding, trusting, disagreeing, scheduling) have a significant influence on a nation's ability and capacity to innovate. The findings show that cultural aspects as described by The Culture Map clearly influence the innovativeness of a nation. Based on these findings, tentative recommendations for fruitful monocultural and multicultural teams respectively are given.
Keywords: 650; Culture; Innovation; Innovativeness; Cultural dimensions